Real-life management of gastrointestinal cow’s milk protein allergy in Brazilian infants - C. Rodrigues, Vanessa C.; Fonseca, Marcelo C. M.; Solé, Dirceu; Sanudo, Adiana; B. Morais, Mauro (Allergologia et Immunopathologia, 2025)
Objective: To evaluate physicians’ management of non-immunoglobulin E-mediated gastrointestinal cow’s milk protein allergy (non-IgE-GI-CMPA) in Brazilian infants.Methods: A total of 447 physicians from all the regions of Brazil answered an online questionnaire concerning their management of formula-fed infants with mild-to-moderate (Case 1) or severe (Case 2) clinical manifestations of non-IgE-GI-CMPA.Results: In total, 95.3% and 86.0% of the interviewed physicians in cases 1 and 2 prescribed a cow’s milk elimination diet (p < 0.001). In the initial management, the prescription rates of formulas based on extensively hydrolyzed protein and amino acid were 81.7% and 14.6% for Case 1 and 32.7% and 65.4% for Case 2 (p < 0.001); the percentages of answers for prescriptions of drugs or probiotics were 8.3% and 12.1% in cases 1 and 2 (p < 0.001); and requests for laboratory tests were 12.3% and 37.7 % (p = 0.016). The oral food challenge (OFC) test for the diagnosis of non-IgE-GI-CMPA was indicated by 55.1% and 42.7% of the physicians in cases 1 and 2 (p < 0.001). The OFC test was chosen to assess tolerance development by 92% of the interviewees. Performing the diagnostic OFC (D-OFC) test was positively associated with having board certification in pediatric gastroenterology and < 20 years of professional experience and negatively associated with using baked foods as a protein source in the oral tolerance OFC test.Conclusions: Most interviewees followed the guidelines regarding prescribing an elimination diet; however, many should include the OFC test in diagnosing infants with non-IgE-GI-CMPA. Not performing the D-OFC may have negative consequences on patients and on the public healthcare system.